The Religious Leaders’ Perspectives on Corona Survey: Methods and Key Results - Öhlmann, Philipp (Religions, 2024)
Religious leaders are highly influential actors in many societies across the globe. In the singular global crisis brought upon by the COVID-19 pandemic, their perspective on the pandemic itself but also the post-pandemic future is of high relevance. Against this background, we conducted the Religious Leaders’ Perspectives on Corona Survey, a comprehensive survey of 1200 religious leaders globally, in 2020/2021. Its aim was to investigate the role of religious communities and religious leaders during the COVID-19 pandemic. This article provides an in-depth outline and discussion of the survey methodology and the resultant dataset, thereby paving the way for future research using the survey data. Moreover, the first set of key results is highlighted. It emerges that the COVID-19 pandemic was not primarily a health crisis. Rather, in terms of its consequences, COVID-19 had the characteristics of a primarily economic crisis in the Global South and a primarily psychosocial crisis in the Global North. Moreover, the pandemic has had a fundamental impact on religious practice across the globe. This impact, however, seems to be highly unequal between the Global South and North. Religious communities are shown to have had an important role as civil society actors in the pandemic, providing both psychosocial and material support. Regarding the post-pandemic world, religious leaders envision a more equitable society and emphasize the need for environmental sustainability.